PTH-083 Should inappropriate 5-asa use in crohn's disease be identified: a preliminary cost analysis. (17th June 2017) - Ramdeen, M; Fenyvesi, A; Chhaya, V
Abstract : Introduction: Crohn's disease is one of the inflammatory bowel diseases and affects around 1 15 000 people in the United Kingdom (UK). The treatment for CD is a rapidly evolving field with substantial healthcare cost. Historically, 5-Aminosalicylic acids (5-ASA) were used in the treatment of CD. However, over the last decade the evidence base has changed and they are no longer recommended for induction or maintenance of remission in CD (Dignass et al, 2010). Our aim was to evaluate the number of CD patients maintained on 5-ASAs in the outpatient setting despite the lack of evidence to support their use and the potential cost implications. Method: We performed a prospective audit using a predesigned proforma. This included patient demographics, disease location as per the Montreal classification, brand of 5-ASA, dose of the 5-ASA, duration of usage, duration of diagnosis and any other medication the patient was using to treat their CD. The audit was undertaken in the IBD Clinical Nurse Specialist (CNS) clinic for a period of eight weeks. Results: During this period a total of 120 patients were seen in the clinics. More than half (55.8%) had a diagnosis of Ulcerative Colitis (UC) while 53 patients (44.1%) had a diagnosis of CD. Almost half (26=49%) of the patients with CD were using a 5-ASA either as monotherapy or combination therapy with an immunosuppressant (IM) and/or a biologic. The majority of these patients were found to have started the 5-ASA at the time of their diagnosis and despite escalation to IM or biologic therapy; the 5-ASA drug was not withdrawn from the treatment regime. We obtained the annual cost breakdown per patient using the specific brand name of 5-ASA and this was followed by a total annual cost (ć35, 067.84) for the 26 patients identified. The average cost for treating one patient with a particular 5-ASA at a dose of 4.8gms daily for one month is ć117.00 with an average total annual cost of ć1, 404.00. Conclusion: In view of the lack of evidence for the use of 5-ASA in CD we estimated a cost saving of approximately ć35 000 per annum in this small cohort of patients identified. We plan to re-audit and perform a further retrospective analysis for stopping treatment in those patients using a 5-ASA in CD and evaluate the cost implications of this. As part of the discontinuation process we will counsel our patients and gradually withdraw their 5-ASA therapy. Reference: . Dignass A, Van Assche G, Lindsay JO, Lćmann M, Sćderholm J, Colombel JF, Danese S, D'Hoore A, Gassull M, Gomollćn F, Hommes DW, Michetti P, O'Morain C, Oresland T, Windsor A, Stange EF, Travis SP. European Crohn's and Colitis Organisation (ECCO): The second European evidence-based Consensus on the diagnosis and management of Crohn's disease: Current management. Journal of Crohn's and Colitis 2010;4(1):28–62. Disclosure of Interest: None Declared